Thrombolysis for acute ischemic stroke by tenecteplase in the emergency department of a Moroccan hospital - Belkouch, Ahmed (Pan Afr Med J, 2015)
INTRODUCTION: Thrombolysis has radically changed the prognosis of acute ischemic stroke. Tenecteplase is a modified form of rt-PA with greater specificity for fibrin and a longer half-life. We report the experience of a Moroccan tertiary hospital in thrombolysis using Tenecteplase. METHODS: We conducted an open prospective study of all patients who were treated with Tenecteplase for an acute ischemic stroke admitted to our emergency department. Tenecteplase was administered intravenously at a dose of 0.4 mg/kg single bolus. The primary outcome measure was the proportion of patients achieving significant early neurological recovery defined as an improvement of 4 or more points on the NIHSS score at 24h. RESULTS: 13 patients had been treated by intravenous thrombolysis. 31% were women. Mean age was 63 years old. The mean NIHSS score at admission was 14.3 and 24h after was at 9.1. The right middle cerebral artery was involved in 69% of cases. The carotid atherosclerosis was predominant 63.3% and the cardio embolic etiology 27%. The mean time to the first medical contact after the onset of symptoms was 3h 30 min. One patient presented a capsulo-lenticular hematoma of 5 mm(3) in the same side of the ischemic stroke. CONCLUSION: Tenecteplase is a more interesting thrombolytic than alteplase, it seems to be more suitable for thrombolysis in our center.